2022
DOI: 10.3390/vaccines10060956
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity Evaluating of the Multivalent COVID-19 Inactivated Vaccine against the SARS-CoV-2 Variants

Abstract: It has been reported that the novel coronavirus (COVID-19) has caused more than 286 million cases and 5.4 million deaths to date. Several strategies have been implemented globally, such as social distancing and the development of the vaccines. Several severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have appeared, such as Alpha, Beta, Gamma, Delta, and Omicron. With the rapid spread of the novel coronavirus and the rapidly changing mutants, the development of a broad-spectrum multivalent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For example, a trivalent vaccine developed by combining the Sinopharm HB02 antigen, and Delta-and Omicrontargeting antigens, could induce bNABs in mice against all variants tested including HB02, Beta, Delta and Omicron. 74 Likewise, another trivalent vaccine targeting ancestral, Beta and Delta spike proteins induced the production of bNABs in mice against all COVID-19 variants tested. 75 The vaccine candidates most advanced in the development pathway are from Moderna and Pfizer-BioNTech.…”
Section: Bivalent and Multivalent Vaccinesmentioning
confidence: 99%
“…For example, a trivalent vaccine developed by combining the Sinopharm HB02 antigen, and Delta-and Omicrontargeting antigens, could induce bNABs in mice against all variants tested including HB02, Beta, Delta and Omicron. 74 Likewise, another trivalent vaccine targeting ancestral, Beta and Delta spike proteins induced the production of bNABs in mice against all COVID-19 variants tested. 75 The vaccine candidates most advanced in the development pathway are from Moderna and Pfizer-BioNTech.…”
Section: Bivalent and Multivalent Vaccinesmentioning
confidence: 99%
“…The authors clarified that cellular immune responses could work in their inactivated vaccines, but the mechanism remained to be studied. 116 Moreover, the RBD‐dimer protein subunit vaccine ZF2001 could exhibit a broadly neutralizing antibody response against five VOCs (Alpha, Beta, Gamma, Delta, and Omicron) and three other variants of interest (VOIs) (Epsilon, Eta, and Kappa). 65 , 117 , 118 At present, ZF2001 has been used in China and several other countries.…”
Section: Broad‐spectrum Anti‐coronavirus Vaccinesmentioning
confidence: 99%
“…Thus, multiple studies have been conducted to develop multivalent vaccines against SARS-CoV-2. Compared with monovalent vaccines, multivalent SARS-CoV-2 vaccines not only induce better immunogenicity against Omicron but also provides more effective protection against other variants ( 108 111 ) ( Table 4 ). Notably, mRNA-1273.214 vaccine which was prepared from ancestral Wuhan-Hu-1 and Omicron B.1.1.529 spike protein mRNAs can induce strong neutralizing antibody responses to Omicron BA.4 and BA.5 subvariants ( 110 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, multivalent SARS-CoV-2 vaccines development is considered to play a constructive role in defending against the constantly mutating virus. Notably, a study found that the HB02 + Beta + Delta + Omicron tetravalent vaccine had lower neutralizing antibody titers against most variants than the trivalent vaccine ( 108 ). This seems to suggest that the immunogenicity produced by multivalent vaccines is not only related to the number of polymerized antigens but also to the ratio of antigen during the preparation process.…”
Section: Introductionmentioning
confidence: 99%